Thyrotoxic crisis presenting with jaundice. (December 2016) - Wickramasinghe, R.; Luke, W.; Sebastiampillai, B.; Gunathilake, M.; Premaratna, R.
Abstract Background Thyrotoxic crisis is a medical emergency requiring early diagnosis and urgent management, which can be challenging due to its diverse clinical presentations. While common presentations include fever, sweating, palpitations, tremors and confusion, presence of jaundice is rare. Case presentation We report a 35-year-old male who presented with jaundice due to cholestasis along with other features of thyrotoxic crisis due to Graves' disease. He had a good clinical recovery with resolution of cholestasis following treatment for thyrotoxic crisis. Conclusion Jaundice can be a rare manifestation of thyrotoxic crisis, and should be considered in the differential diagnosis when other clinical features of thyrotoxic crisis are present. However secondary causes of jaundice should be looked into and excluded.